The Effect of Corporate Social Responsibility (CSR) Activities on Companies With Bad Reputations - Yoon, Yeosun; Gürhan‐Canli, Zeynep; Schwarz, Norbert (Journal of Consumer Psychology, 2006)
Based on theories of attribution and suspicion, three experiments highlight the mediating role of perceived sincerity of motives in determining the effectiveness of CSR activities. CSR activities improve a company's image when consumers attribute sincere motives, are ineffective when sincerity of motives is ambiguous, and hurt the company's image when motives are perceived as insincere. Variables affecting perceived sincerity include the benefit salience of the cause, the source through which consumers learn about CSR, and the ratio of CSR contributions and CSR‐related advertising. High benefit salience of the cause hurts the company, in particular when consumers learn about it from a company source. This backfire effect can be overcome by spending more on CSR activities than on advertising that features CSR.